Technologies for Teaching Mathematics in a Multilingual Digital Environment - Galina Dubinina; Larisa Konnova; Irina Stepanyan (MDPI AG, 2022)
The article considers the expansion of digital technologies and their impact on training modern specialists. The increase in the volume of information, students' requests for interdisciplinary practice-oriented training, and the involuntary transition to online learning during the COVID-19 pandemic encouraged changes in the ways educational information is presented. The multilingual approach, enhanced by digitalization, also contributes to these transformations. The purpose of this study is to develop a methodology aimed at improving the perception and understanding of mathematics. The experience of combining digital training in mathematics, multilingual technologies and scaffolding is considered. Scaffolding is implemented in a digital environment and is extended by the reverse scaffolding approach, when the educational material first appears without prompts, and then the prompts are given from complex to simple. Based on the idea of presenting information in various ways, a test was created on the Moodle LMS platform. The surveys showed that the current generation of students prefers educational information based on visualization and supporting symbolic signs. When presenting new material and generating training tests, the teacher should refer to inter-subject multilingualism, reinforcing it with a professional context. Digital implementation of scaffolding proved to be especially in demand during the transition to online learning.